Ground beetle (Coleoptera: Carabidae) fauna of two oak woods in the area with two different water balances - Vujčić-Karlo, Snježana (Acta entomologica slovenica (Ljubljana), 2004)
The community structure of ground beetles had been explored on two sampling sites within the Zoological reserve Varoški Lug, situated in the plain part of Croatia at an average altitude of 105 m. Two plant subcommunities have been chosen for research: Genisto elate-Quercetum roboris caritetosum remotae (VL1) and Genisto elate-Quercetum roboris caritetosum brizoides (VL2) from the order Populetalia albae. 29 species of ground beetles with 6469 specimens have been recorded. The dominant species are Carabus ullrichi, C. granulatus, C. violaceus, Pterostichus melas and Abax parallelus. Although the distance between the sampling areas is very short and there are no obstacles which could prevent the mixing of the faunas of the two sites, their fauna is different. This difference is evident from species which inhabit the certain site, but especially by the population abundance and the annual cycles. The diversity of both communities is very high but it is higher at the site VL2. The site VL1 has acid soil with high moisture due to the underground waters especially in spring and summer. The soil at the site VL2 is pseudogley characterized by the occasional moisture with different duration of the dry and the moist phase. Once or twice a year the site VL1 is flooded. Water in the soil is an ecological factor which influences the ground beetle fauna the most, so it is possible that longer retention of water at the site VL1 is less favourable to the species dominant at the site VL2. The share of the flying species is high in both communities. Since the sampling sites are surrounded by open biotopes there is also a great number of species inhabiting open habitats or the species indifferent to the shaded habitats. The high underground waters combined with the continental climate are favourable to the hygrophilic species. The annual cycles of the beetle numbers at the site VL1 shows greater regularity than that at the site VL2. The maximum specimen activity of all species at the site VL1 is in May and June. After that the number of specimens rapidly drops. The number of beetle specimens of all species at the site VL2 is high during the whole year. The activity starts in April and lasts till September.
Keywords: Croatia; favna; hrošči; Hrvaška; insekti; krešiči; populacijska dinamika; zoogeografija